Coaching drills & performance enhancement skills in swimming - Sweetenham, NB.; Goldsmith,W.; Richards, R. (coachesinfo.com)
This article is intended to build upon the coach's knowledge of basic coaching concepts, esp. drills. To incorporate the basic principles of motor learning and neuromuscular adaptation drills must be applied in a progressive sequence. This is a total swimming progression which combines all the skills taught to the swimmer throughout their career . The progression is designed in a logical, methodical manner, to build from stroke basics to stroke refinements. These progressions must also incorporate the co-ordination of movements, timing, and fitness of the upper body and the lower body musculature. Too many freestyle and backstroke swimmers are upper body dependent; while breaststrokers may tend to become lower body dependent. Drills should have the capacity to strengthen areas of weakness and maximise the strengths, whilst co - ordinating the effective interaction between upper and lower body. The value of drills does not diminish as a swimmer's career progresses. Coaches at the senior level must take the time, through one-on-one coaching contact, to "fine tune" a swimmer's stroke. Formula one racing cars do not come off an assembly line; precision and attention to detail, refinement, and evaluation are all components of a long-term strategy for stroke development. The coach must also pay close attention to the precision of drill application. Because drills tend to focus attention on components of the total stroke, it's possible to target inherently weak points of the stroke pattern; such as the hand entry or exit (i.e. extremities of the stroke). As with any movement, if the start is made correctly (i.e. movement pattern plus correct positioning of the body) there is a better chance that the continuation of the movement will be correct. The coach must never overlook the integration of movements (i.e. for efficient propulsion) and positioning of all segments of the body (i.e. for reduction of resistance) when evaluating the effectiveness of a drill. Regardless of type of drill, these ten guidelines can be applied: 1. A drill done 100% right is 100% right, and a drill done 99% right is 100% wrong. (i.e. one percent separates champions and would be champions). 2. Drills represent an effective tool for isolating the difference between propulsion and resistance. It's essential that both factors work in harmony and that improvement in one does not sacrifice the other (i.e. propulsive force without proper streamlining is wasted and great streamlining without propulsion is ineffective). 3. Swimming is a technique driven sport. Differences between elite swimmers will usually be the result of technique and skill differences, rather than major training differences (i.e. for example: all elite sprinters are quick and powerful, not allof them control and use their resources by applying that power with technique). Great swimmers do not train with poor technique. Part of their greatness comes from the desire to be the best they can be; they will expect more of themselves than the work the coach has set. 4 . For every technique fault there is a drill to correct it, for every drill there is another drill to correct the fault within the drill (i.e. no drill is perfect). If you're looking for a magic cure to every stroke problem, there is none! 5 .Teaching drills correctly is like teaching completely different strokes (i.e. the drills themselves become sets of complex motor patterns). If you have four key drills for each stroke, in effect you have to teach 20 different strokes; that is, the 16 drills plus the four swimming strokes. (Thanks to coach Phil King for this idea.) Quality, not quantity, is the hallmark of effective use of drills. The better the overall teaching standard and methodology, from learn-to-swim onwards, the less likely you are to rely on drills. Learn-to-swim progressions, stroke development drills, stroke correction drills, and linking drills all contribute to the end result - a swimmer who is able to properly absorb the benefits of training because he/she applies optimal technique. 6 .The quality of previous instruction/coaching and a swimmer's talent determines the amount of attention to technique required at the present (or next) stage of development (i.e. the requirements of swimmers will vary). 7. New drills should be taught near the beginning of a session when the swimmers' minds and bodies are most receptive to learning. Once drills are learned they are applied during the training session to achieve the desired affect. Sometimes it's best to practise drills under conditions of fatigue which closely resemble actual race conditions. 8.The brain will learn the correct and incorrect technique equally well. In the early stages of learning, correct the swimmer by providing positive constructive feedback as often as possible. Lack of supervision or quality control at any step makes the next step more demanding or more difficult. It's also important to maintain the quality of previous skills as a drill progresses or moves to the next step. 9 . Design training sets which reinforce the skills learned in drills (i.e. if your drill improves the turn or finish, then allow swimmers enough space in the lane to practice those skills during the training sets). 10 . Always have a long-term plan of swimmer development. Establish a learning and skill development progression through drills which includes: 1 Introduction of a skill and quality practice until mastery, 2 Practice the skill under a performance criteria (i.e. such as, minimum stroke count), 3 Practice the skill with a time limit (i.e. repeat drills on 1min.30sec. holding times which are below 200m race pace), 4 Practice the skill with both performance criteria and time limits (i.e. repeats on 1min.30sec. holding race simulated stroke count and speed). ! Drills are about performing fewer strokes with precise effort and concentration in each stroke. Drills have nothing to do with easy swimming.!